A educação matemática e o cuidado de si: possibilidades foucaultianas - Silva, Michela Tuchapesk da [UNESP] (2014)
In line with the Philosophy of Difference, this research puts into practice the transverse movements contrary to the vertical and horizontal movements in school with the goal of presenting discussions about the possibilities of mathematics teachers in regard to the 'autonomy', the 'self-care' according to Michel Foucault (2005, 2006, 2007, 2010). For this, we made use of the method of cartography - related to the human subjectivity - investigating the practices and techniques of subjectivism of the self in accordance with the ethics of Foucault's individual. Thus, in a public school in Sao Paulo state countryside we held theoretical and practical workshops with a group of nine math teachers, aiming at the possibility of creating new ways of existence, new subjectivity, moving concepts and other thoughts such as: what are the possibilities of being a teacher? Do mathematics teachers take autonomous decisions, i.e., taken by themselves? Or do they work on the common sense as automatic pilots? Do teachers have control of their school practices and tactics? Or are the teachers controlled by the mainstream power and knowledge? Will the power always manipulate us? Is there resistance in schools? Or we can trace other pathways in education; pathways to permanent resistance and discussion? Therefore, these workshops were strong enough to establish a new territory in education. Contrary to a vertical or horizontal territory, the power of transverse movement produced almost rhisomatically escape routes, new ways of existing, different perspectives and some other thoughts